Shifting towards market-oriented irrigated crops development as an approach to improve the income of farmers: Evidence from northern Ethiopia - Woldewahid, G.; Gebremedhin, Berhanu; Berhe, Kahsay; Hoekstra, Dirk (International Livestock Research Institute, 2011)
Rainfed crop production in the semi-arid areas is associated with high risk of rainfall variability which occasionally leads to complete crop failure. Most of the farmers in Atsbi-Womberta district of Eastern Tigray region, northern Ethiopia, have been classified as food insecure. To improve farmers’ livelihoods in the district, interventions targeted at resource conservation and better use of conserved water for market-oriented irrigated crops development have been promoted. This paper analyses the process and outcome of shifting towards market-oriented irrigated crops development and compares variation in income between beneficiary and nonbeneficiary households. The transformation processes are based on market-oriented diversification into high value irrigated crops, based on a value chain approach, and demand driven, participatory and knowledge based extension. The paper also assesses the response of smallholder farmers to emerging opportunities and challenges, and the spectrum of transformation processes and strategies followed to bring changes in smallholder farmers’ income. The changes associated with the interventions were systematically captured using household level surveys, specialized studies and key informant interviews. Results show that farmers gradually shifted to non-cereal, more market-oriented irrigated crops, in which the share of market-oriented irrigated crops increased from 27% of the total irrigated land in 2004 to 89% in 2009. Similarly, the total irrigated area increased by about fourfold and the number of beneficiaries by about threefold due to improved use of conserved surface and groundwater, and investment in farmer skills and water lifting devices. Moreover, crop diversification and intensification of households increased in response to emerging opportunities and challenges. Annual cropping intensity shifted from mono-crop cereal to 2–3 high value diversified crop farming by some farmers. On aggregate, average income of beneficiary households increased by about ninefold compared to non-beneficiary households. In the transformation, there have been continuous and interconnected processes and strategies in improving the effectiveness of adopting and using new skills and knowledge in harvesting and productive use of water, and responsive capacity of the extension system and partners. The lessons imply that investment in resources conservation could be enhanced if linked with short-term income generating activities through linkages with markets.